Improved explosion resistance of low cement refractory castables using drying agents. Issue 2 (3rd February 2022) - Peng, Hong; Myhre, Bjørn
Abstract: Low cement castables (LCCs) containing different types of drying agents (polymer fibers and EMSIL‐DRY ™ ) have been studied both in laboratory‐ and industrial‐scale. Our study shows that the type of drying agent has a profound impact on the flow/workability of the fresh castables and that EMSIL‐DRY ™ ensures the best workability. The thermal behavior of 300 mm cubes (approximately 80 kg) was studied using a unique macro‐thermo‐balance (macro‐TGA). Compared to the polymer fibers, EMSIL‐DRY ™ reduces the temperature level for maximum dewatering rate and will effectively help prevent explosions during heat‐up. The LCC with EMSIL‐DRY ™ showed excellent explosion resistance, as demonstrated by the production of a perfect 400 kg block that was fired to 850°C at a rate of 75°C/h.